Uji Ketahanan Beberapa Calon Varietas Jagung Manis (Zea mays L. saccharata Sturt.) Hibrida F1 UNSIKA Terhadap Penyakit Penting Jagung di Purwakarta - Dimaspatti, Satrio; Syafi’i, Muhammad; Afifah, Lutfi; Rakhman, Fathu (JURNAL AGROPLASMA, 2023)
One of the causes of the decreased production of sweet corn (Zea mays L. saccharata Sturt.) is the attack  by disease. Some important diseases that attack sweet corn is leaf blight and leaf rust. Use of hybrid varieties one of the solution which can be used to reduce the crop loss caused by disease. This study aimed to testing the level of resistance of sweet corn hybrid candidates against important corn disease. The research was conducted in the Ambu Garden, Pusakamulya Village, Kiarapedes sub District, Purwakarta District, from July 2021 to September 2021. The design used was a non-factorial randomized block design (RAK) with 33 genotypes of prospective hybrids and 3 commercial comparison varieties and 3 replications. The test result on leaf blight and leaf rust there are several hybrids candidate shows a resistant to moderately resistant reaction. From testing against leaf blight, there are 8 hybrids candidate showed a resistant reaction to moderately resistant. The test result against leaf rust disease, there are 9 hybrids candidate showed resistant to moderately resistant reaction. Overall, the test results against leaf blight disease and leaf rust disease there are  six candidates of sweet corn hybrids that show resistant reaction against both disease, there is UNSIKA 33, 35, 36, 37, 41, and 44 with an average attack intensity of 20,00%. Keywords: Hybrid varieties,Leaf blight, Leaf rust, Sweet corn